Ответ:
(2а + 4)(5а + 6) = 10а² + 32а + 24
(2х² - 1)(х + 3) = 2х³ + 6х² - х - 3
(3у² + 5)(у - 6) = 3у³ - 18у² + 5у - 30
(7с² - 1)(с - 3) = 7с³ - 21с² - с + 3
Нижнюю строчку слов я не смог перевести
Если переведешь, то я сделаю
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
(2а + 4)(5а + 6) = 10а² + 32а + 24
(2х² - 1)(х + 3) = 2х³ + 6х² - х - 3
(3у² + 5)(у - 6) = 3у³ - 18у² + 5у - 30
(7с² - 1)(с - 3) = 7с³ - 21с² - с + 3
Нижнюю строчку слов я не смог перевести
Если переведешь, то я сделаю